Outer-sphere Electron Transfer in the Systems Tri(Naphtho- quinoneoximato) Iron(III)/Oximes or Metal Dithizaonates - Al-Qurashi, M.A.; Aly, A.A.M. (Asian Journal of Chemistry, 2012)
Mixing the solutions of tris(naphthoquinoneoximato) iron (III) with the solutions of various oximes in different solvents produces colour change attributable to outer-sphere transition from the oximines to the iron(III) naphthoquinoneoximate complex. The interaction of tris(naphthoquinone-oximato) iron(II) is also observed with the complexes of dithizonate, where a charge transfer (CT) band is recorded upon mixing solution of the iron complex and Ni(HDz)2, Cu(HDz)2, and Zn(HDz)2. A detailed analysis of the outer-sphere absorption bands leads to some important conclusions. The Hush theory is adopted to deduce optical and thermodynamic parameters.